Determination and evaluation of in vitro bioaccessibility of added vitamin C in commercially available fruit-, vegetable-, and cereal-based baby foods - Ugur, Halime; Catak, Jale; Mizrak, Omer Faruk; Cebi, Nur; Yaman, Mustafa (ELSEVIER SCI LTD, 2020)
Knowing the bioaccessibility of vitamin C in foodstuffs produced for infants and young children is necessary to determine their daily vitamin C intake. The purpose of the present study was to investigate the bioaccessibility of vitamin C in fruit-, vegetable-, and cereal-based baby foodstuffs by an in vitro digestion model at varying gastric pHs. The concentrations of measured vitamin C were higher than the declared amounts on their label. The bioaccessibility of vitamin C ranged from 10.4 to 43.4%, and from 0.4 to 19.2% in fruit-and vegetable-based baby foodstuffs (declared vitamin C fortified) at gastric pH 1.5 and 4, respectively. For cereal-based baby foodstuffs, the bioaccessibility ranged from 1.3 to 53.8%, and from 0.3 to 26.3% at gastric pH 1.5 and 4, respectively. As revealed in this research, the bioaccessibility of vitamin C in baby foodstuffs is very low in both gastric pH conditions.
Keywords: Baby foods; Fruits; Vegetables; Cereals; Vitamin C; Bioaccessibility; Nutrition; GASTROINTESTINAL DIGESTION; ASCORBIC-ACID; PHENOLIC-COMPOUNDS; CHILDREN; CAROTENOIDS; BROCCOLI; Chemistry; Food Science & Technology; Nutrition & Dietetics